Perancangan Rebranding Logo Pantai Joko Mursodo - Adwitiya, Fairuzah Nafisah; Wulandari, Sri; Ayuswantana, Alfian Candra (Universitas Pahlawan Tuanku Tambusai, 2024)
Joko Mursodo Beach, as a tourist destination in Lamongan Regency, has great potential but is constrained by weaknesses in visual identity that are not yet strong and consistent. The lack of coordinated branding planning as well as the lack of implementation of a clear visual identity in various media are major obstacles. The lack of information conveyed to tourists through social media is also a problem, resulting in low public and tourist awareness of the potential of the beach. In this design, qualitative methods are implemented by conducting interviews, observations, and distributing questionnaires to the community. The data was then analyzed using a descriptive approach as well as the TOWS model. Therefore, the rebranding of Joko Mursodo Beach is needed to create a strong and attractive image. This will be achieved through the development of structured designs, improvement of promotional media, and delivery of more complete and interesting information. These steps aim to increase public awareness and the attractiveness of Joko Mursodo Beach as an attractive tourist destination.